CONCEPTUALIZING THE UNDERSTANDING OF PROFESSIONAL IDENTITY IN TEACHERâ€™S CAREER - Mikelsone, Ilze; Odina, Indra; Grigule, Ligita (European Scientific Journal, ESJ, 2014)
The article deals with the research designed as the Grounded Theoryto explore and conceptualize the practising teachersâ€™ perception of their professional identity. The practising teachers â€“ master students of the professional master study programme â€žTeacherâ€ study module â€œEducation for Well-being and Cohesionâ€ taking the course â€žEducatorâ€™s Professional Identity and Pedagogic Masteryâ€ were chosen to help to formulate the theory. Analogies (metaphors) and narrative essays have been used as the techniques for identifying concepts. Making associations, brainstorming, coding, making concepts, conceptual sorting in categories, memoing and outlining theories was the procedure how teachers conceptualized the various elements used to construct professional identity.Word frequency list and keyword- in-context list techniques were used to carry out computer-aided content analysis and represented by the help of Wordle.net â€“ the tool for generating â€œword cloudsâ€ from text that is provided. The outcome of this research is the content of teachersâ€™ professional identity discussed and analysed in the light of various theories and in close link with the concepts of â€œprofessional careerâ€, â€œpersonality developmentâ€, â€œcareerâ€ and â€œself-conceptâ€. Based on the keywords provided by teachers, the teacherâ€™s professional identity structure consisting of 4 components: professional â€œself-conceptâ€, harmony of professional identity, successful self-determination and creative professional activity was elaborated by adding criteria notions, as well as the content analyses of teachersâ€™ narratives was used to identify professional identity development statuses.